Atomistic simulation of oxide materials with catalytic properties - Măicăneanu, A. (Department of Environmental and Ordnance Systems, 2009)
When supported, thin films demonstrate remarkable structural transformations, with important implications for catalysis, sensors, electrochemistry, semiconductors or superconductors. At present, the tools available to characterize solid-solid systems cannot provide atomic level resolution of, for example mixed screw-edge dislocations. Therefore atomistic simulation can provide an invaluable complement to experiment. In this work atomistic simulation was employed to generate models of oxide thin films. First an atom deposition methodology was used to create an SrO thin film on a BaO(001) support. The evolution of the thin film from small clusters (submonolayer coverage), to five atomic layers, which includes cracks in its structure, was studied. Specifically, information related to growth and nucleation processes can be explored using this methodology. Secondly an amorphisation and recrystallisation methodology was developed to explore the more complex system, that of ceria deposited on zirconia and yttrium stabilized zirconia. Simulated amorphisation and recrystallisation involves forcing the thin film to undergo a transformation into an amorphous state prior to recrystallising and therefore the recrystallisation process rather than the (perhaps artificial) initial structure will dictate the final structure. The recrystallisation process enables the evolution of all the important structural modifications as the thin film evolves structurally in response to the support. These include dislocations (pure edge and mixed screw-edge), dislocation networks, grain-boundaries and defects (interstitials, vacancies and substitutionals, including complex defect association) all within a single simulation cell.